2014
DOI: 10.1007/s00404-014-3469-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal age and parity on maternal and neonatal outcome

Abstract: AMA, especially primiparous, has more adverse maternal and neonatal outcomes than younger women; however, these did not include mortality. Consistent antenatal care may explain this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
109
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 36 publications
17
109
3
5
Order By: Relevance
“…[14][15][16] This finding is also similar to that of a previous study using the same primiparous model, 4 which reported that the aORs of LBW <2,500 g and PTB before 37 weeks were significantly increased in the 30-34-, 35-39-, and ≥40-year age groups. However, since we analyzed a larger number of participants and included psychological distress, measured using the K6 score, in logistic model than in that study, the aOR of PTB before 37 weeks and LBW <2,500 g in each age group was similar but the aOR of LBW <1,500 g became higher in our study.…”
Section: Discussionsupporting
confidence: 88%
“…[14][15][16] This finding is also similar to that of a previous study using the same primiparous model, 4 which reported that the aORs of LBW <2,500 g and PTB before 37 weeks were significantly increased in the 30-34-, 35-39-, and ≥40-year age groups. However, since we analyzed a larger number of participants and included psychological distress, measured using the K6 score, in logistic model than in that study, the aOR of PTB before 37 weeks and LBW <2,500 g in each age group was similar but the aOR of LBW <1,500 g became higher in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Since both maternal age and parity correlate with higher birth weight, LGA rate, and other maternal pathology, such as hypertension or placenta previa [3,[36][37][38][39] we matched the controls to the study groups in order to exclude the possible bias. According to Lintsen et al, the impact of smoking on the live birth rate in IVF treatment is comparable with an increase in female age of >10 years in young women [40].…”
Section: Discussionmentioning
confidence: 99%
“…As well as the risks of ovarian stimulation and oocyte collection, studies are consistent as to the increase in perinatal (pre-eclampsia, maternal hypertension, preterm labour, perinatal mortality) and maternal risks (operative delivery and maternal morbidity and mortality) with advanced maternal age at delivery (50 years and 3 months in this case [15][16][17][18]). Specifically assessing the more extremes of maternal age, Laopaiboon et al [15] demonstrated adjusted odds ratios of 3.7 for a severe maternal adverse outcome (defined as a maternal death or a maternal near-miss up to 7 days after giving birth) and 1.6, 1.9 and 2.1 for a low Apgar score at delivery, perinatal mortality and stillbirth in women 45 or over at delivery.…”
Section: Discussionmentioning
confidence: 65%
“…Specifically assessing the more extremes of maternal age, Laopaiboon et al [15] demonstrated adjusted odds ratios of 3.7 for a severe maternal adverse outcome (defined as a maternal death or a maternal near-miss up to 7 days after giving birth) and 1.6, 1.9 and 2.1 for a low Apgar score at delivery, perinatal mortality and stillbirth in women 45 or over at delivery. Schimmel et al [16] demonstrated a significant increase in maternal hypertension (7.3 vs. 4.7 %), maternal diabetes (11.7 vs. 1.2 %), emergency operative delivery (0.9 vs. 0.3 %) and preterm delivery (5.2 vs. 4.0 %) in those between 43 and 47 compared to those 24-27. Data from the EUROCAT registries of congenital anomaly demonstrate that although overall congenital anomalies increase with age, there is no significant increase in nonchromosomal anomalies [19].…”
Section: Discussionmentioning
confidence: 98%